Tick-borne disease control: the role of impact assessment - Perry, Brian D. (International Livestock Research Institute, 1996)
In a world of ever-increasing competition for resources, human, economic and environmental, it is now more important than ever before that a thorough understanding is acquired of the effect of large-scale interventions to relieve constraints to livestock production, such as disease control programmes. This is in order that the impacts of such actions can be defined not only in biological efficacy terms (the focus of the paper by Morzaria in these proceedings), but also in terms of the improvements in livestock productivity, and in terms of socio-economic and environmental impacts the programmes will have. In the case of tick-borne infections of livestock, which are widely distributed in Africa and many other tropical and sub-tropical regions of the developing world, their effect on livestock productivity varies widely by production system, agroecological zone, and other factors. It is thus important to define clearly their impact under priority production systems, such as smallholder dairy enterprises, and determine the impact of interventions to control them. This will help identify priority populations at which to target tick-borne disease control technologies as well as demonstrate to farmers, implementing groups and donors the value of investing in such interventions. At ILRI, a systems analysis and impact assessment research group exists, with the responsibility of evaluating the impact of priority constraints to livestock productivity, and predicting the impact of new technologies under development at the institute to relieve these constraints. The group operates by developing strategic impact assessment models, with the collaboration of selected national agricultural research system (NARS) institutes as case studies, and of advanced research institutes with expertise in model development. This framework permits the progressive improvement of model quality and capacity, the enhancement of data sets on impacts, and the use of models in some countries to determine the impact of specific constraints. This frame work has been applied in particular to determining the impact of theileriosis and its control through immunisation, and the host country for this workshop, Zimbabwe, has been an active collaborator in this research.